2017
DOI: 10.1109/jsen.2017.2703601
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Compensation Mechanism Between an NMR Gyroscope and an SERF Gyroscope

Abstract: Through analysis of the compensation mechanism of nuclear-magnetic-resonance (NMR) gyroscope and spinexchange-relaxation-free (SERF) gyroscope, we demonstrate that there is a common model for these two kinds of an atomic rotation rate sensor. The output signals of NMR and SERF gyroscopes are compared directly, which provides a guidance for the scheme choosing and optimization of atomic gyroscope. The input-output relation of both gyroscopes is given, which can be used to analyze the contributions of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Figure 20 and Figure 21 display the performer's head towards the camera, even when it should be facing away the camera when performing the movement "Walking backwards". An alternative solution to the problem faced by Kinect sensor as suggested by the 3D animation expert is using multiple Kinect sensors to get better motion data or using more advanced motion tracking system such as marker based motion capture system with cameras "Optitrack" (name of a brand) or markered based motion capture system with gyroscope sensors [19] without any camera for a more affordable alternative. This motion capture system with gyroscope is also equipped by accelerometer and magnetometer.…”
Section: Results Analysismentioning
confidence: 99%
“…Figure 20 and Figure 21 display the performer's head towards the camera, even when it should be facing away the camera when performing the movement "Walking backwards". An alternative solution to the problem faced by Kinect sensor as suggested by the 3D animation expert is using multiple Kinect sensors to get better motion data or using more advanced motion tracking system such as marker based motion capture system with cameras "Optitrack" (name of a brand) or markered based motion capture system with gyroscope sensors [19] without any camera for a more affordable alternative. This motion capture system with gyroscope is also equipped by accelerometer and magnetometer.…”
Section: Results Analysismentioning
confidence: 99%
“…A gyroscope is utilised to estimate the angular speed and support maintain direction in navigation applications [16,17]; it is typically combined with an accelerometer to construct the inertial navigation system. The main gyroscope frame consists of a gimbal and a rotor, where the spin axis is free to represent any orientations without interference from tilting and rotations.…”
Section: Wearable Sensors: Basic Informationmentioning
confidence: 99%
“…By contrast, the coating performance is mainly measured by the relaxation time of the alkali metal vapor cell through optical quantum detection [14][15][16][17]. Seltzer successfully developed an alkali test cell to test the antirelaxation properties of surface coatings and found that the antirelaxation quality changes as a function of temperature [7].…”
Section: Introductionmentioning
confidence: 99%